1978
DOI: 10.1073/pnas.75.10.4793
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic conversion of 5'-phosphate-terminated RNA to 5'-di- and triphosphate-terminated RNA.

Abstract: We have isolated from vaccinia virus cores an enzyme, 5'-phosphate-polyribonucleotide kinase, that in the presence of ATP and Mg2+ catalyzes the conversion of 5'-phosphate and 5'-diphosphate termini of RNA to the 5'-triphosphate species. With the exception of dATP, other nucleoside triphosphates were inactive as hosphate donors; activity with dATP was 10%o of that observed with ATP The purified enzyme did not phosphorylate 5'-hydroxyl-or 5'-monophosphate-terminated polydeoxyribonucleotides, although a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…To be capped, the 5Ј-monophosphate end would have to be converted to a di-or triphosphate by a polynucleotide 5Ј-monophosphate kinase. The only reports of such an activity were published more than 30 years ago (23,27). Given these points, we suspected that the previous study identified some other type of modification that behaved like a cap.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…To be capped, the 5Ј-monophosphate end would have to be converted to a di-or triphosphate by a polynucleotide 5Ј-monophosphate kinase. The only reports of such an activity were published more than 30 years ago (23,27). Given these points, we suspected that the previous study identified some other type of modification that behaved like a cap.…”
Section: Discussionmentioning
confidence: 83%
“…These data also suggest that a kinase capable of converting 5Ј-P-RNA into a diphosphate capping substrate was recovered with immunoprecipitated cytoplasmic capping enzyme. Evidence for such an enzyme was described more than 30 years ago (23,27), but there are no contemporary reports. This was examined by incubation of the beads containing immunoprecipitated GFP, mCE, or K294A used for Fig.…”
mentioning
confidence: 99%
“…These characteristics raise the question of whether such capped 5Ј ends were generated by nonstringent transcription initiation, posttranscriptional mechanisms, or imperfect CAGE methodology. With regard to posttranscriptional mechanisms, there is evidence for secondary recapping of processed RNAs in the cytoplasm (24,41,45) and a 5Ј-phosphate polynucleotide kinase was isolated from VACV cores (54). Few TSSs with relatively low read counts were mapped antisense to VACV ORFs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mRNAs that are decapped or cleaved by endonucleases are produced as pRNAs and thus need to be converted to diphosphorylated RNAs (ppRNAs) to be capped by a guanylyltransferase. The existence of pRNA kinase in mammalian cells has been proposed (16,17) and such an activity has been found in the cytosol, complexed with a guanylyltransferase (18). However, the responsible protein has not yet been identified.…”
mentioning
confidence: 99%